Understanding the complex role of mTORC as an intracellular critical mediator of whole-body metabolism in anorexia nervosa: A mini review. : Anorexia nervosa and the complex role of mTORC - Alaaraj, Nada; Soliman , Ashraf; Hamed , Noor; Alyafei , Fawziya; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2021)
Summary. Anorexia nervosa (AN) is a kind of malnutrition resulting from chronic self-induced starvation. The reported associated endocrine changes (adaptive and non-adaptive) include hypothalamic amenorrhea, a nutritionally acquired growth hormone resistance with low insulin like growth factor-1 (IGF-1) secretion, relative hypercortisolemia, decreased leptin and insulin concentrations, and increased ghrelin, PYY and adiponectin secretion. The combined effect of malnutrition and endocrinopathy may have deleterious effects on multi-organs including bone, gonads, thyroid gland, and brain (neurocognition, anxiety, depression, and other psychopathologies). The mammalian target of rapamycin (mTOR) is a kinase that in humans is encoded by the mTOR gene. Recent studies suggest an important role of mTOR complex in integration of nutrient and hormone signals to adjust energy homeostasis. In this review, we tried to elucidate the role/s of mTOR as critical mediator of the cellular response in anorexia nervosa.